NMR Studies of Active‐Site Properties of Human Carbonic Anhydrase II by Using 15N‐Labeled 4‐Methylimidazole as a Local Probe and Histidine Hydrogen‐Bond Correlations. Issue 7 (17th December 2014) - Shenderovich, Ilya G.; Lesnichin, Stepan B.; Tu, Chingkuang; Silverman, David N.; Tolstoy, Peter M.; Denisov, Gleb S.; Limbach, Hans‐Heinrich
Abstract By using a combination of liquid and solid‐state NMR spectroscopy, 15N‐labeled 4‐methylimidazole (4‐MI) as a local probe of the environment has been studied: 1) in the polar, wet Freon CDF3/CDF2Cl down to 130 K, 2) in water at pH 12, and 3) in solid samples of the mutant H64A of human carbonic anhydrase II (HCA II). In the latter, the active‐site His64 residue is replaced by alanine; the catalytic activity is, however, rescued by the presence of 4‐MI. For the Freon solution, it is demonstrated that addition of water molecules not only catalyzes proton tautomerism but also lifts its quasidegeneracy. The possible hydrogen‐bond clusters formed and the mechanism of the tautomerism are discussed. Information about the imidazole hydrogen‐bond geometries is obtained by establishing a correlation between published 1H and 15N chemical shifts of the imidazole rings of histidines in proteins. This correlation is useful to distinguish histidines embedded in the interior of proteins and those at the surface, embedded in water. Moreover, evidence is obtained that the hydrogen‐bond geometries of His64 in the active site of HCA II and of 4‐MI in H64A HCA II are similar. Finally, the degeneracy of the rapid tautomerism of the neutral imidazole ring His64 reported by Shimahara et al. (J. Biol. Chem. 2007, 282, 9646) can be explained with a wet, polar, nonaqueous active‐site conformation in the inward conformation, similar to the properties of 4‐MI in the Freon solution. The biological implications for the enzyme mechanism are discussed.